2021
DOI: 10.3389/fcell.2021.753787
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of G Protein-Coupled Receptors in 20-Hydroxyecdysone Signaling From the Helicoverpa armigera Genome

Abstract: G protein-coupled receptors (GPCRs) are the largest family of membrane receptors in animals and humans, which transmit various signals from the extracellular environment into cells. Studies have reported that several GPCRs transmit the same signal; however, the mechanism is unclear. In the present study, we identified all 122 classical GPCRs from the genome of Helicoverpa armigera, a lepidopteran pest species. Twenty-four GPCRs were identified as upregulated at the metamorphic stage by comparing the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In addition, the family of Methuselah genes is known to be involved in longevity and stress resistance [141]. Recent work in Lepidoptera suggests that GPCRs with homology to the Methuselah family of receptors may play important, unresolved roles in mediating the key hormone ecdysone [63], [142]. Importantly, it has been shown that mthl-8 is a potential target of the JNK signaling in the Drosophila eye disc [143].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the family of Methuselah genes is known to be involved in longevity and stress resistance [141]. Recent work in Lepidoptera suggests that GPCRs with homology to the Methuselah family of receptors may play important, unresolved roles in mediating the key hormone ecdysone [63], [142]. Importantly, it has been shown that mthl-8 is a potential target of the JNK signaling in the Drosophila eye disc [143].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, chromosome 1 exhibited the highest density of GPCR genes with nine members. Conversely, chromosomes 12,13,17,19,22,23, and 24 demonstrated relatively low gene density, with no more than two genes present on each. Furthermore, utilizing MCScanX analysis, three instances of tandem duplication events were detected among the octopamine receptor genes, RYamide receptor genes, and Mthls (Figure 1).…”
Section: Identification Of Gpcr Genes In C Pomonellamentioning
confidence: 96%
“…The presence of such genetic diversity, both in terms of genotype and quantity, contributes to the distinct functional characteristics observed across different insect species . For instance, Bombyx mori , Helicoverpa armigera , and Spodoptera frugiperda have been found to possess 93, 122, and 167 GPCRs, respectively. This variation in the number of genes is proposed to have arisen as an adaptive response to varying environmental pressures. Based on sequence similarity and functional properties, the identified GPCRs in insects are categorized into four families: rhodopsin-like receptors (Class A), secretin receptors (Class B), metabotropic glutamate/pheromone receptors (Class C), and frizzled/smoothened GPCRs (Class F) .…”
Section: Introductionmentioning
confidence: 99%
“…Wnt signaling starts when the “N‐terminal cysteine‐rich extracellular domain of a Fz family receptor” is bound by a Wnt protein (Chae & Bothwell, 2018). These Fz family receptors span the plasma membranes by sevenfold and constitute a different “G‐protein coupled receptors” (GPCRs) family (Awuchi, 2023; Kramer et al, 2017; Li et al, 2021; Takahashi et al, 2017). Nevertheless, co‐receptors may be required to encourage Wnt signaling along with the interactions between the Fz receptor and the Wnt proteins.…”
Section: Introductionmentioning
confidence: 99%